O controle do TCU sobre as minutas de editais de licitação em concessões de serviço público federais: um estudo sobre a impossibilidade jurídica dessa atuação - Bianca Rocha Barbosa (2023)
The goal of this research is to explore the debate if the Federal Audit Court (TCU) can inspect the drafts of bidding documents for federal public service concessions before their publication. First, the study investigates if the Court has the right to do so based on the Constitution or based on other ordinary legislation. Furthermore, it evaluates if the Federal Audit Court could support its conduct solely on infra-legal norms of its own authorship, as it currently does. Next, it is analyzed whether, from a legal and conceptual point of view, it is possible for the Court to exercise control over the preparatory phase of the auctions. Moreover, the work determines that the TCU, improperly, assigns itself competence and authority to inspect preliminary bidding documentation, overly expensing its powers. Finally, it concludes saying that TCU cannot control the planning phase of the public services concession bidding process because it invades the administrative discretion jurisdiction. The research was methodologically developed in a legal-dogmatic approach and is of the legal-comprehensive or legal-interpretative type.